Changes in the Value of Exports of Agricultural Products from Selected ACP Countries - Chryniewicz, Łukasz (Zeszyty Naukowe SGGW w Warszawie - Problemy Rolnictwa Światowego, 2015)
The process of globalization creates and stimulates the network of mutual economic and trade relations between countries through cooperation within international organizations. Export of agricultural products has a measurable and significant impact on the development of world trade, and therefore it is important to examine the changes that have occurred in exports of selected ACP countries from 2002 to 2013.